Resin komposit glass ionomer lebih menghambat pertumbuhan Streptococcus mutans daripada resin komposit konvensional secara in vitro - Sari Kusumadewi (Bali Dental Journal, 2019)
Introduction: Composite resin is one of the most common materials used in dentistry. Some modifications have been done to the resin matrix and fillerin order to solve the secondary caries problem. A recent development is resin composite containing glass ionomer filler particles. The purpose of this study is to examine the antibacterial activity of composite resin containing glass ionomer filler particles to Streptococcus mutans compared with conventional composite resin in vitro. Method: This study was an experimental study with randomized post test only control group design. This study has been done in Microbiology Laboratory, Faculty of Medicine, Udayana University. The subjects of this study were Streptococcus mutans ATCC 35668, conventional composite resin and composite resin containing glass ionomer filler particle. Some composite resins were placed in Mueller Hinton Agar, then incubated for 24 hours. Datas were tested normality by Shapiro-Wilk test and homogenity by Levene’s test, then tested using One Way ANOVA and continued with post-hoc test to seek the differences between in pair between group.Result: The result showed the formation of clear zone around each sample, with diameter in control group was 4.23 mm, conventional resin composite group was 8,31±0,10 mm and glass ionomer resin composite was 11.77±0.16 mm. The diameter in glass ionomer composite resin seemed wider than conventional composite resin. Conclusion: It is concluded the difference in diameter were resulted from four factors such as type of filler, size of filler, the amount of fluor, and the initial fluoride burst effect.